2020
DOI: 10.3390/v12010092
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ebola Virus Disease (EVD) in Rhesus Monkeys for Development of EVD Therapeutics

Abstract: Recent Ebola virus (EBOV) outbreaks in West Africa and the Democratic Republic of the Congo have highlighted the urgent need for approval of medical countermeasures for treatment and prevention of EBOV disease (EVD). Until recently, when successes were achieved in characterizing the efficacy of multiple experimental EVD therapeutics in humans, the only feasible way to obtain data regarding potential clinical benefits of candidate therapeutics was by conducting well-controlled animal studies. Nonclinical studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
6
14
0
Order By: Relevance
“…Additionally, genes relating to coagulation and hypoxia were upregulated to a greater extent in this species (e.g., ADAM8, TREML1, FCGER1). These transcriptional findings are consistent with exaggerated coagulopathy and hepatocellular damage (e.g., more severe loss of platelets and higher levels of AST) in rhesus compared to cynomolgus macaques reported in previous studies [28,29].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, genes relating to coagulation and hypoxia were upregulated to a greater extent in this species (e.g., ADAM8, TREML1, FCGER1). These transcriptional findings are consistent with exaggerated coagulopathy and hepatocellular damage (e.g., more severe loss of platelets and higher levels of AST) in rhesus compared to cynomolgus macaques reported in previous studies [28,29].…”
Section: Discussionsupporting
confidence: 91%
“…Both species are equally susceptible to EBOV infection; however, differences in the duration/severity of EVD and histopathological presentation exist. Importantly, time to euthanasia following infection with a lethal dose of EBOV-Mayinga or EBOV-Makona is shorter in cynomolgus macaques (5-6 days) compared to rhesus macaques (~8 days) [26][27][28][29]. This is accompanied by earlier changes in inflammatory mediators, earlier onset of viremia and greater severity of cellular stress and coagulopathy (e.g., elevated BUN, CRE, and AST; reduced PLT) in rhesus macaques [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVD progression in animals on this study was similar to previously reported studies [ 21 , 22 , 23 ]. The first indication of infection was detection of the viral NP gene in blood at two days post-exposure (summary in Figure 4 ).…”
Section: Discussionsupporting
confidence: 91%
“…Among them, NHPs are considered the "gold standard" animal model since they are highly susceptible to the infection of wild-type EBOV (WT-EBOV) that have been isolated from human samples. Nearly all clinical and pathological features of severe/fatal EVD in humans can be recapitulated in NHPs, including high viremia, strong cytokine/chemokine response, coagulopathy, rash, and hemorrhagic signs [71][72][73][74][75]. Cynomolgus and rhesus macaques have been the most commonly used NHPs for EBOV infection; disease progression in cynomolgus macaques after EBOV infection is slightly faster than that in rhesus macaques [6].…”
Section: Ebov Pathogenesis Studied In Animal Modelsmentioning
confidence: 99%